Trends in Television Da'wah Research in Indonesia - Mochamad Syaefudin; Andi Faisal Bakti; Arif Zamhari; Nani Kurniasari (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
This study aims to identify and analyze the trend of television da'wah studies in Indonesia using a systematic literature review (SLR) approach. A total of 153 articles were initially identified, of which 20 articles met the inclusion criteria and were included in the final analysis of television da'wah published in the 2009–2023 period. The analysis uses the selection, classification of themes, and synthesis of findings. The results of the study show that 65% of articles still focus on the conceptual aspects of television da'wah, especially related to history, the characteristics of television as a da'wah medium, and the role of da'wah actors. Meanwhile, 25% of the research focused on the issue of the commodification of da'wah including the formation of new religious authorities and audience responses to television da'wah content that tends to prioritize entertainment over educational functions. In contrast, only 10% of the studies examined the use of information and communication technology in television da'wah, showing a significant research gap. These findings have theoretical implications for the need to develop a framework for studying television da'wah that is not only oriented to normative approaches and media political economy, but also integrates communication technology perspectives. Practically, this study provides recommendations for media practitioners and producers of Islamic religious programs to optimize the use of digital technology to improve the quality, interactivity, and educational function of Islamic religious programs on television. The novelty of this research lies in the systematic mapping of the technological gap in Islamic religious programs on Indonesian television, which can be the basis for further research and development of Islamic religious programs on television that are adaptive to the digital era.